2014
DOI: 10.3349/ymj.2014.55.2.428
|View full text |Cite
|
Sign up to set email alerts
|

Single Nucleotide Polymorphisms of Toll-Like Receptor 7 and Toll-Like Receptor 9 in Hepatitis C Virus Infection Patients from Central China

Abstract: PurposeTo analyze the correlation of polymorphisms of toll-like receptor 7 (TLR7) (rs179009) and toll-like receptor 9 (TLR9) (rs187084) in hepatitis C virus (HCV) infections in the Han population.Materials and MethodsThe genotypes of TLR7IVS2-151 in HCV infection were detected by Sanger sequencing using polymerase chain reaction-restriction fragment length polymorphism to determine the TLR9 T-1486C single nucleotide polymorphisms (SNP) for all enrolled patients.ResultsWe found no significant difference between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 34 publications
1
19
1
Order By: Relevance
“…Although Wei et al 40 conducted a similar study in chronically infected Chinese patients with HCV, they did not observe an association which may be due to their small cohort size.…”
Section: Discussionmentioning
confidence: 84%
“…Although Wei et al 40 conducted a similar study in chronically infected Chinese patients with HCV, they did not observe an association which may be due to their small cohort size.…”
Section: Discussionmentioning
confidence: 84%
“…Similarly, Wei and others showed no significant association with regard to TLR-9 (rs187084) genotype and allele frequency between chronic HCV patients and subjects who spontaneously cleared the virus. 38 In humans, TLR-3-promoter region is responsible for maintenance of promoter integrality and promoter-specific virus responsive element. 39 In our study, the TLR-3 (_7 C/A) SNP within the promoter region is not associated with HCV infection, and our results are comparable to results in other ethnicities.…”
Section: Discussionmentioning
confidence: 99%
“…However, patients with fatal cases of CCHF have a 7.63‐fold greater frequency of the GG genotype of TLR7 c.4‐151 A/G polymorphism (Table ). Wei et al [] found that the relationship between the TLR7 c.4‐151 A/G polymorphism and patients infected with HCV (hepatitis C virus) is dependent on gender. In one study it was revealed that TLR 7 has a considerable role in HCV infection because ssRNAs can be bound by TLR 7, giving rise to the production of high levels of the antiviral cytokine interferon‐α by DC [Colonna et al, ].…”
Section: Discussionmentioning
confidence: 99%